Toronto - Johnson, Lorraine; Hopkinson, Barbara; Gale Group (London Dorling Kindersley Limited, 2015)
Provides background information on Toronto. Recommends the 10 best restaurants, bars, nightlife, neighborhoods, hotels, and local attractions.
Toronto's top 10 -- Around town -- Streetsmart.
"ISSN: 1479-344X."
Includes bibliographical references and index.
Keywords: Toronto (Ont.) -- Guidebooks